(untitled) (Global Journal of Medical Research, 2014)
Pseudomonas aeruginosa is an opportunistic pathogen, frequently associated with nosocomial infections worldwide. Multiple drug resistance has been reported in previous studies against pathogenic P. aeruginosa and the biofilm which makes use of antibiotics futile. Bacteriophages specific for P. aeruginosa can prove to be a new therapeutic approach for controlling infections and biolfilm contamination against this pathogen. The aim of our study was to isolate and partially characterize virulent phage specific for P. aeruginosa from sewage water. Different parameters of which make phages as suitable candidate towards future therapeutics were also investigated. Phages having lytic life cycle, high burst size and thermally more stable proposed themselves as effective therapeutic candidates. In this study, a virulent phage was isolated from sewage water having burst size of 1036 and latent period of 21 minutes. This phage has narrow host range and shows the remarkable thermal resistance and is viable up to 60 ºC.